Impact of wind waves on the air‐sea fluxes: A coupled model. Issue 2 (20th February 2014) - Kudryavtsev, V.; Chapron, B.; Makin, V.
Abstract A revised wind‐over‐wave‐coupling model is developed to provide a consistent description of the sea surface drag and heat/moister transfer coefficients, and associated wind velocity and temperature profiles. The spectral distribution of short wind waves in the decimeter to a few millimeters range of wavelengths is introduced based on the wave action balance equation constrained using the Yurovskaya et al. (2013) optical field wave measurements. The model is capable to reproduce fundamental statistical properties of the sea surface, such as the mean square slope and the spectral distribution of breaking crests length. The surface stress accounts for the effect of airflow separation due to wave breaking, which enables a better fit of simulated form drag to observations. The wave breaking controls the overall energy losses for the gravity waves, but also the generation of shorter waves including the parasitic capillaries, thus enhancing the form drag. Breaking wave contribution to the form drag increases rapidly at winds above 15 m/s where it exceeds the nonbreaking wave contribution. The overall impact of wind waves (breaking and nonbreaking) leads to a sheltering of the near‐surface layer where the turbulent mixing is suppressed. Accordingly, the air temperature gradient in this sheltered layer increases to maintain the heat flux constant. The resulting deformation of the air temperature profile tends to lower the roughness scale for temperature compared to its value over the smooth surface.